2013
DOI: 10.1016/s0168-8278(13)61313-6
|View full text |Cite
|
Sign up to set email alerts
|

1312 Pioglitazone Upregulates Angiotensin Converting Enzyme 2 Expression in Insulin-Sensitive Tissues in Rats With High Fat Diet-Induced Non-Alcoholic Steatohepatitis

Abstract: Background and Aim. Thiazolidinediones (TZDs) can improve hepatic steatosis in nonalcoholic steatohepatitis (NASH). Angiotensin (Ang) II, the primary effector of renin-angiotensin system (RAS), plays vital roles in the development and progression of NASH. And some AngII-mediated effects can be regulated by TZDs. Angiotensin-converting enzyme (ACE) 2, a new component of RAS, can degrade Ang II to attenuate its subsequent physiological actions. We aimed to evaluate the effects of TZDs on ACE2 expression in insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Individuals with diabetes mellitus not only have increased susceptibility to but also higher morbidity and mortality due to coronavirus disease 2019 (COVID-19).The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses angiotensin converting enzyme (ACE)2 as a co-receptor to enter the cell [ 1 ]. Among anti-diabetic agents, liraglutide and pioglitazone [ 2 ], and among anti-hypertensives, ACE inhibitors (ACEi)/angiotensin receptor blockers (ARB) [ 3 ], have been shown in some animal studies to upregulate the tissue expression of ACE2. This has led to the speculation that use of these medications might increase susceptibility to, and severity of, COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with diabetes mellitus not only have increased susceptibility to but also higher morbidity and mortality due to coronavirus disease 2019 (COVID-19).The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses angiotensin converting enzyme (ACE)2 as a co-receptor to enter the cell [ 1 ]. Among anti-diabetic agents, liraglutide and pioglitazone [ 2 ], and among anti-hypertensives, ACE inhibitors (ACEi)/angiotensin receptor blockers (ARB) [ 3 ], have been shown in some animal studies to upregulate the tissue expression of ACE2. This has led to the speculation that use of these medications might increase susceptibility to, and severity of, COVID-19.…”
mentioning
confidence: 99%
“…Recent publications have alluded to upregulation of ACE2 by pioglitazone [ 7 ]. Indeed, animal studies have shown that pioglitazone increases the expression of ACE2 in the liver, adipose tissue and skeletal muscles [ 2 ]. However, pioglitazone was found to have no effect on cardiac ACE2 expression in a study on db/db mice [ 8 ].…”
mentioning
confidence: 99%